PROGRAM KEBUN GIZI KELUARGA MAPAN (MANDIRI PANGAN) DI ECO SCHOOL NUSANTARA SEBAGAI UPAYA PENCEGAHAN STUNTING DI DESA SENGKOL, LOMBOK TENGAH - Uzlifatul Azmiyati; Baiq Dewi Sukma Septiani; Wardatul Jannah (Jurnal Abdi Insani, 2023)
Problematic nutrition, especially in children, is the forerunner to other, more serious problems, namely stunting. Meeting the nutritional needs of families is often hampered by the assumption that the food used must be expensive and difficult to obtain. In fact, these foods will be easier to obtain if you grow them yourself in your yard. So that it can be used as a nutritional garden that supports food independent families. The aim of this activity is to form community groups that use their yards to become nutritional gardens, process organic waste to be used in nutritional gardens so that food independence is formed at the household scale. The activity method begins with providing education on healthy and balanced nutrition as well as education on nutritional gardens and organic waste processing to achieve the activity objectives. Before education is carried out, a location survey and focus group discussion with partners are carried out. And participants' knowledge was measured using a posttest. The results of the activity showed that there was an increase in participants' knowledge after providing education on balanced nutrition and health. This is proven by the results of the bivariate test analysis that has been carried out. Participants were enthusiastic and immediately put into practice the knowledge gained from educational activities. Through this activity, community groups have been formed who use their yards as nutritional gardens. Furthermore, community groups were formed that were able to process organic waste by utilizing kitchen waste to support nutritional gardens. As well as increasing public understanding about healthy and balanced nutrition. This can be a basis for preventing stunting in Sengkol Village. The conclusion of this activity is the formation of community groups that use yards as nutritional gardens, are able to process organic kitchen waste to support nutritional gardens, and increase community knowledge about healthy, balanced nutrition and the environment.